2001
DOI: 10.1038/sj.cr.7290074
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 over-expression and activation of protein kinase C suppress the Trail-induced apoptosis in Jurkat T cells

Abstract: Trail, a tumor necrosis factor-related apoptosis-inducing ligand, is a novel potent endogenous activator of the cell death pathway through the activation of cell surface death receptors Trail-R1 and Trail-R2. Its role, like FasL in activation-induced cell death (AICD), has been demonstrated in immune system. However the mechanism of Trail induced apoptosis remains unclear. In this report, the recombinant Trail protein was expressed and purified. The apoptosis-inducing activity and the regulation mechanism of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Bcl-2, a 26 kDa protein, is predominantly localized to the cytoplasmic face of the mitochondria outer membrane, endoplasmic reticulum, and nuclear envelope. Bcl-2 seems to prevent apoptosis induced by many stimuli, for example, irradiation, FasL [26], TRAIL [27] and deprivation of growth factor, and it has been shown to suppress cytochrome c (cyt.c) efflux from mitochondria, inhibit calcium release from the endoplasmic reticulum [24,28,29]. Others have speculated that Bcl-2 regulates the generation of reactive oxygen radical since Bcl-2 is able to attenuate cell death induced by oxidative damaging agents [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, a 26 kDa protein, is predominantly localized to the cytoplasmic face of the mitochondria outer membrane, endoplasmic reticulum, and nuclear envelope. Bcl-2 seems to prevent apoptosis induced by many stimuli, for example, irradiation, FasL [26], TRAIL [27] and deprivation of growth factor, and it has been shown to suppress cytochrome c (cyt.c) efflux from mitochondria, inhibit calcium release from the endoplasmic reticulum [24,28,29]. Others have speculated that Bcl-2 regulates the generation of reactive oxygen radical since Bcl-2 is able to attenuate cell death induced by oxidative damaging agents [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that the intrinsic mitochondrial pathway is also involved in SG235-TRAIL-induced apoptosis of leukemic cells evidenced by the activation of caspase-8 and caspase-9, decreased Bid, and dysfunction of mitochondria. Moreover, Bcl-2 family proteins are critical for the determination of sensitivity to TRAIL (28,29). Recent studies have shown that degradation of Mcl-1, a Bcl-2 family member, initiates mitochondrial apoptotic cascade (42).…”
Section: Discussionmentioning
confidence: 99%
“…A number of stimuli, including stress, chemotherapeutic agents and UV radiation, appear to induce apoptosis via mitochondrial pathway [3,16,17]. In the present studies, the molecular changes related to the mitochondrion-regulated apoptotic pathway in TCtreated CHO cells were analyzed.…”
Section: Tc Induced Apoptosis Of Cho Cells Through the Mitochondrion-mentioning
confidence: 94%